Analysis of foot kinematics during toe walking in able-bodied individuals using the Oxford Foot Model. Issue 8 (11th June 2022) - Lee, Wonhee; Yoo, Beomki; Park, Dongho; Hong, Juntaek; Shim, Dain; Choi, Joongon; Rha, Dong-wook
Abstract: Various neurological and musculoskeletal disorders can induce pathologic toe walking and lead to changes in foot kinematics. In this study, we analyzed the differences in foot kinematics between toe walking and heel-toe walking (HW) in able-bodied individuals. Twenty young healthy adults performed three gaits: HW, comfortable-height toe walking (CTW), and maximum-height toe walking (MTW). Oxford Foot Model was used for gait analysis. Toe walking showed increase of forefoot plantarflexion and hindfoot internal rotation compared to HW. Thus, our results may help distinguish the pathologic mechanism of the equinus gait in various disorders from the kinematic change of toe walking itself.